The Use of Technology in Akidah Akhlak Instruction: Opportunities and Challenges in the Digital Era - Muhammad Abdun Jamil (PT. Anagata Sembagi Education, 2024)
This study investigates the impact of technology on akidah akhlak(Islamic theology and morality) instruction in Islamic schools. The background of this research lies in the increasing use of technology in education and its potential to improve both student engagement and understanding of religious values. The study aims to explore how interactive applications like Quizizz can enhance the teaching and learning process in akidah akhlak classes, as well as identify the challenges faced in technology implementation. Using a descriptive qualitative approach, data were collected through observation, interviews, documentation, and questionnaires. The findings show that the use of technology significantly improves student motivation and understanding, making the learning process more interactive and engaging. However, challenges such as limited infrastructure and the readiness of both students and teachers to adopt technology were also noted. These challenges highlight the need for strategic planning and investment in infrastructure and teacher training to fully realize the potential of technology in akidah akhlak instruction.